2022
DOI: 10.1101/2022.08.13.503869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sweat and sebum preferences of the human skin microbiota

Abstract: The microorganisms that inhabit human skin, collectively termed the skin microbiome, must overcome numerous challenges that typically impede microbial growth, including low pH, osmotic pressure, and low nutrient availability. Yet, the skin microbiota thrive on the skin and have adapted to these stressful conditions. Limited skin nutrients are available for microbial use in this unique niche, including those from host-derived sweat, sebum, and corneocytes. Here, we have developed physiologically-relevant, skin-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…This set of genomes includes 22 genomes we had previously described as part of the complex 11 . In addition, we added three recently reported metagenome-assembled genomes (MAGs) from skin predicted to correspond to novel Corynebacterium species 14 and the genome of a C. kefirresidentii we recently isolated from human skin 9 . All 26 genomes, including a total of 8 MAGs, were regarded as high completion and showed low rates of contamination by CheckM analysis 15 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This set of genomes includes 22 genomes we had previously described as part of the complex 11 . In addition, we added three recently reported metagenome-assembled genomes (MAGs) from skin predicted to correspond to novel Corynebacterium species 14 and the genome of a C. kefirresidentii we recently isolated from human skin 9 . All 26 genomes, including a total of 8 MAGs, were regarded as high completion and showed low rates of contamination by CheckM analysis 15 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of genomes for the species complex, despite its prevalence on healthy skin, might be in part due to difficulties with culturing. For instance, we recently found that a single C. kefirresidentii isolate grows best when high concentrations of compounds found in both sebum and sweat are available 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations